The Security Landscape of Human Protection from the International Law Perspectives on Case of the New-Taliban-Afghanistan State - Amaritasari , Indah Pangestu; Sugiharto, Sri Bagas (Jurnal Keamanan Nasional, 2022)
Post-Cold War security in international relations is identified as security in the global contemporary. Contemporary global issues are closely related to issues that are no longer dominated by East-West relations, such as the threat of nuclear war, ideological competition between Liberal-Democracy and Marxism-Leninism, crisis diplomacy, and so on. From the perspective of liberalism, peace and security are important for the international system, and being considered by international law and organizations. However, recent developments in Afghanistan and Ukraine mark a challenge to this idea and challenge the consistency of peace and security under international law. This study uses the EUD (Explore, Understanding, and Doing) method to analyze the security context and the juridical-normative research to understand the international law that contributes to the aspect of security. The security landscape from the perspective of International Law is fragile against minorities and vulnerable groups because gaining power, in relation ot effective control doctrine in international law, does not necessarily associate to the security of human protection as the case happened in the new-Taliban-Afghan State.